(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Tutsi, the Twa and the Hutu are three social groups that have enjoyed a monoculture and lived on the same land. In 1994, around one million Tutsi were killed in a genocide organised by the then interim government. It is almost impossible to find any category of people who resisted participating in these killings, which have had tremendous long-lasting consequences. The extent of the killings made the genocide against the Tutsi one of the most researched topics in the history of Rwanda. However, only a few studies have focused on the teaching of this topic. In this article, I argue that the teaching of the genocide against the Tutsi is not an easy task because the teacher has to be careful not only in the choice of the methodology but also in selecting words to be used in a history class and taking into consideration the Rwandan socio-political context. In order to understand the phenomenon of teaching the genocide against the Tutsi, this study adopted a qualitative approach with a career life story methodology. This approach helps us to understand one history teacher’s views on his experience of teaching the aforementioned phenomenon. The selected teacher’s views cannot be generalised. However, they can give insight into the situation. Rukundo is one of the eleven Rwandan history teachers interviewed in 2013 and again in 2020 in Rwanda during and after my PhD research. This story was chosen because Rukundo is one of the four out of eleven history teachers who indicated that they predominantly used the learner-centred approach recommended by the 2008 and 2010 history curricula and the current competence-based curriculum. The choice of the above participant can help the readers to understand not only the complexity of teaching the genocide against the Tutsi in history in Rwandan secondary schools but also the way the career life story used in this article was constructed to explain Rukundo’s lived experience.